RESEARCH ON BODY DONATION WILLINGNESS IN CORDOBA-ARGENTINA: MEDICAL AND DENTIST DOCTORS ATTITUDE - Susana N. Biasutto; Oscar P. David; Marcos A. Spinelli; Daniel Urrutia; Atilio J. Bertocchi Valle; Diego M. Weigandt; Isaías E. Molina Vargas; Ramiro A.A. Vargas; Lucia M. Navarro; Sofía G. Siemsen; Florencia Turri; Nicolás Longoni; et al. (Asociación Argentina de Anatomía Clínica, 2019)
Medicine and Dentistry are the only careers performing human body dissection and teaching-learning of Anatomy with cadaveric material in our university. Physicians and dentists' knowledge and opinion on the topic are particularly important because they could be considered as potential procurators due to their contact and influence on patient's decisions. We surveyed 528 professionals (429 physicians and 99 dentists) collecting some demographic data and questions about organ and whole body donation. Results showed that 94% should donate organs for transplantation, 66% knew about body donation, 66% was interested in further information and 48% should be willing to donate the own body for teaching and research. Main reasons to donate were to support teaching and research, contribute to the science and to be useful. In conclusion, we found that professionals had a very positive attitude in relation to body donation, independently of gender, age, religion, regional origin or specialities, but with significant differences between physicians and dentists. Compared with students, they had better attitude which could be related to a better information and experience. In comparison with the few published articles we found, our results were similar to Ireland and very different to India, improving our expectances about the success of developing a donation program. Organ and body donation are always an act of altruism and social solidarity.